Modelling computational thinking with game-based learning among primary school students’ - Mohamed, Zulkifley; Ubaidullah, Nor Hasbiah; Junus, Noor Wahida Md; Angamuthu, Kasthuri Devi; Ahmad, Ahmad (Institute of Advanced Engineering and Science, 2024)
The computational thinking (CT) skills of students will be revised, increasing their future viewpoint in the sphere of scientific activities, notably in education interest. Game-based learning (GBL) appears to have the potential to improve students’ motivation to learn. Students’ GBL is associated with higher mathematics performance, and GBL’s strong relationship with CT may have an even larger effect. The entirety of this CT education research is focused on undergraduate classrooms; little is revealed about how GBL support CT in K-12, particularly in primary schools. This study utilized a Structural Equation Model (SEM) in modelling the relationship between CT and GBL among primary school students. A sample of 90 primary school students from Malaysia was chosen. In this study, the Partial Least Squares-Structural Equation Model (PLS-SEM) was employed to develop the model. The results demonstrate that empirical evidence, coupled with prior observations verified the model developed. The developed model successfully confirmed all the indicator variables stated in the constructs as all of the associations within the model were significant. In conclusion, the lower order components (LOC) along with the hierarchical component model (HCM) in PLS-SEM depicted the relationship between CT and GBL, substantiated empirically.